PENERAPAN METODE LEAST COST TERHADAP PENDISTRIBUSIAN AIR GALON GUNA EFISIENSI BIAYA TRANSPORTASI(Studi kasus : Depot air Bunga Jayapura) - Rahmat Hidayat; Kymi Rian Febrian, Rizka Amelia Putri, Imanuel Nahum Ketjeway, Revol Raiwaki, Heru Sutejo (CV. ADIBA AISHA AMIRA, 2025)
The distribution of refillable gallon drinking water is a vital component of the logistics system for essential community needs. Efficiency in distribution, particularly transportation cost efficiency, is key to ensuring all demand is met at the lowest possible cost. This study aims to evaluate the cost efficiency of transportation distribution from Depot Bunga in Entrop, Jayapura, to three demand points: Gang Kelor, Gang Jambu, and Gang Kelapa, using a transportation model with the Least Cost method. This method is selected for its simplicity and effectiveness in producing an initial allocation solution that is close to optimal. The data used include the delivery capacity of three couriers, the demand at each gang, and the cost per delivery route. The results show that all demand is fulfilled with optimal utilization of each courier’s capacity, and the minimum distribution cost reached is IDR 202,000. This study confirms that the Least Cost method can serve as a practical basis for effective and efficient daily distribution decision-making in small and medium-sized businesses